Fitrah Based Education: Kesadaran Orang Tua Menumbuhkan Fitrah Keimanan Anak - umroh, hayail (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
A child since being born into the world is understood to bring the attributes that are still in the form of seeds or forerunners which are later referred to as potential, and it is the duty of parents to grow them, but there are still many parents who are not aware of this, so neglect and guidance in trying to cultivate these attributes do not occur. The research method used is qualitative which explains comprehensively by presenting the object of the problem in Fitrah Based Education, then the technique of collecting documentation data from relevant libraries which is analyzed descriptively. As a result of the research, parents need to be made aware that this faith needs to be nurtured from an early age through consistent religious education and positive spiritual experiences. The importance of role models in worship and noble character is an important aspect in shaping children's character. In addition, parents need to be actively involved in family religious activities, such as congregational prayers, reading the Qur'an together, and celebrating Islamic religious holidays.